Growth, yield and nutrients uptake as influeneed by different planting methods in safed musli ( chlorophytum borivilianum) - CHANDRA, RAM; KUMAR, DINESH; AISHWATH, O P (The Indian Journal of Agricultural Sciences, 2011)
An experiment was conducted during 2002-2003 and 2003-2004 at Anand, Gujarat, to study the effect of different planting methods (ridge and furrow, double row raised bed and triple row raised bed methods) on growth, yield and nutrients uptake of safed musli (Chlorophytum borivilianum Santapau and Fernandes). In double row raised bed method, leaf area, root weight/clump, fresh root yield and N, P and K uptakes were significantly higher as compared to triple row raised bed method. In double row raised bed method the fresh root yield was (2.337 tonnes), and it was 3 1.65 and 14.85 %higher over the triple row raised bed (1 .80 tonnes) and ridge and furrow method (2.06 tonnes) respectively.